2020
DOI: 10.1155/2020/6240687
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Quality and Adherence to Postpolypectomy Surveillance Guidelines in an Underinsured Clinic System

Abstract: Background. Delivery of high-quality colonoscopy and adherence to evidence-based surveillance guidelines is essential to a high-quality screening program, especially in safety net systems with limited resources. We sought to assess colonoscopy quality and ensure appropriate surveillance in a network of safety net practices. Methods. We identified age-eligible patients ages 50-75 within a Federally Qualified Health Center (FQHC) clinic system with evidence of colonoscopy in preceding 10 years. We performed char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…Our results on baseline adherence with colonoscopy surveillance guideline recommendations are consistent with other studies. A study from Austin, Texas, that included 1,709 patient charts (26) found that interval surveillance was clearly stated in 72% of the procedures and that recommended intervals were too short in 24.5% of cases and too long in 3.6% of cases. A multicenter retrospective observational study in 2015 based on US veterans found that the rate of nonadherence to guideline recommendations was 35.8%; this increased to 45%-52% for colonoscopies with hyperplastic or adenomatous polyps (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our results on baseline adherence with colonoscopy surveillance guideline recommendations are consistent with other studies. A study from Austin, Texas, that included 1,709 patient charts (26) found that interval surveillance was clearly stated in 72% of the procedures and that recommended intervals were too short in 24.5% of cases and too long in 3.6% of cases. A multicenter retrospective observational study in 2015 based on US veterans found that the rate of nonadherence to guideline recommendations was 35.8%; this increased to 45%-52% for colonoscopies with hyperplastic or adenomatous polyps (27).…”
Section: Discussionmentioning
confidence: 99%
“… 4 Unfortunately, up to one‐third of patients have unsatisfactory bowel cleansing, 5 , 6 with detrimental effects on colonoscopy completion, endoscopic accuracy, patient tolerance, and healthcare costs. 7 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…4 Unfortunately, up to one-third of patients have unsatisfactory bowel cleansing, 5,6 with detrimental effects on colonoscopy completion, endoscopic accuracy, patient tolerance, and healthcare costs. [7][8][9][10][11] Many products for bowel preparation are available, with polyethylene glycol (PEG)-based formulations the most commonly used in United States and Europe. However, PEG formulations have some disadvantages, including a large volume of solution, unpleasant taste, complicated timing, nocturnal problems (because of the split-dose regimen), and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect colonoscopy quality, including the type of health service organization, type of facility, staff, equipment, patient characteristics, and the bowel preparation (BP) process (Table 2). High‐quality colonoscopy is essential for successful screening programs and effective diagnosis 7,8 . The BP process is especially important 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…High‐quality colonoscopy is essential for successful screening programs and effective diagnosis. 7 , 8 The BP process is especially important. 9 , 10 , 11 Inadequate BP results in a lengthy procedure, incomplete colonoscopy, incorrect diagnosis or diagnostic delay, increased costs due to the need to repeat the procedure, adverse events, and patient unwillingness to repeat the examination.…”
Section: Introductionmentioning
confidence: 99%